2012
DOI: 10.1177/1753193412444399
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic aspects during the cylinder grip — flexion sequence of the finger joints analyzed using a sensor glove

Abstract: The purpose of this study was to assess whether there is a universal pattern of movement of the finger joints while performing a cylinder grip. A sensor glove was used to record the finger joint motion of 48 participants. Our observations showed that when examining the fingers, flexion motion began either at the metacarpophalangeal (MP) or proximal interphalangeal (PIP) joints, with the distal interphalangeal (DIP) joints always last to move (p = 0.0052). The sequence of the joints at the end of the gripping m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…The joint sequence of the thumb is different from that of the long fingers. The MCP-IP sequence occurred most frequently in the thumb flexion in this study, which was also observed during the cylinder grip [34] and during the thumb opposition [44]. Similarly, the probability of the IP-MCP sequence was relatively larger during extension.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The joint sequence of the thumb is different from that of the long fingers. The MCP-IP sequence occurred most frequently in the thumb flexion in this study, which was also observed during the cylinder grip [34] and during the thumb opposition [44]. Similarly, the probability of the IP-MCP sequence was relatively larger during extension.…”
Section: Discussionsupporting
confidence: 72%
“…The results showed that, although the joint sequences were not absolutely identical among all fingers, they shared some commonalities. On the other hand, previous studies have implied that the finger joint sequence would change during the motion process [ 33 , 34 ]. However, no study has fully characterized the joint sequences at the beginning, middle and end of the flexion and extension of fingers.…”
Section: Discussionmentioning
confidence: 99%
“…The joint sequence of the thumb is different from that of the long fingers. The MCP-IP sequence occurred most frequently in the thumb flexion in this study, which was also observed during the cylinder grip [32] and during the thumb opposition [42]. Similarly, the probability of the IP-MCP sequence was relatively larger during extension.…”
Section: Discussionsupporting
confidence: 72%
“…The results showed that, although the joint sequences were not absolutely identical among all fingers, they shared some commonalities. On the other hand, previous studies have implied that the finger joint sequence would change during the motion process [31,32]. However, no study has fully characterized the joint sequences at the beginning, middle and end of the flexion and extension of finger.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation